Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2147/ijgm.s329980
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis and Identification of Genes and Pathways in Ischemic Cardiomyopathy

Abstract: Purpose Ischemic cardiomyopathy (ICM) is considered to be the most common cause of heart failure, with high prevalence and mortality. This study aimed to investigate the different expressed genes (DEGs) and pathways in the pathogenesis of ICM using bioinformatics analysis. Methods The control and ICM datasets GSE116250, GSE46224 and GSE5406 were collected from the gene expression omnibus (GEO) database. DEGs were identified using limma package of R software, and co-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In our study, SERPINA3 and FCN3 were down-regulated in bioinformatics analysis, the external validation data, and the functional experiment of the ICM rat. Jing et al ( 40 ) found that SERPINA3 and FCN3 were identified as the potential biomarkers in ICM using bioinformatics analysis. The validation results of SERPINA3 and FCN3 in myocardial tissue of ICM patients were consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, SERPINA3 and FCN3 were down-regulated in bioinformatics analysis, the external validation data, and the functional experiment of the ICM rat. Jing et al ( 40 ) found that SERPINA3 and FCN3 were identified as the potential biomarkers in ICM using bioinformatics analysis. The validation results of SERPINA3 and FCN3 in myocardial tissue of ICM patients were consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] The expression of MXRA5 mRNA has been observed to be upregulated in cardiac tissue in ischemic cardiomyopathy, and may play an important role in the development and progression of HF. [ 19 ] The MAPK pathway plays a key role in the regulation of cell proliferation, survival, differentiation and apoptosis, and its activation promotes myocardial fibrosis and reduces cardiac function in HF rats. [ 20 ] It has been shown that MXRA5 is closely related to the MAPK pathway, and that MXRA5 promotes cell proliferation and apoptosis through the MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The Database for Metascape ( https://metascape.org/gp/index.html ) is applied to achieve the aim of performing KEGG pathway enrichment analysis and GO, which provides a biologist-oriented resource for the investigation of systems-level datasets. Enriched GO terms and pathways are dealed by utilizing the WeiShengXin tools ( https://www.bioinformatics.com.cn ) which is an online platform free of cost for database analyzing [ 46 49 ] (Figures 7 and 8 ).…”
Section: Methodsmentioning
confidence: 99%